ETNOZOOLOGI: STUDI KEARIFAN LOKAL MASYARAKAT ADAT KAMPUNG NAGA TASIKMALAYA - Yustika Ayu Sekartaji; Diana Hernawati; Vita Meylani (Florea : Jurnal Biologi dan Pembelajarannya, 2021)
Ethnozoological study is a study that examines the relationship between humans and animals in traditional studies. People's knowledge in relation to these animals has been passed down from generation to generation to become local wisdom. This ethnozoology includes the matter of raising animals, managing animals for medicine, food and customary and ritual activities, as well as the reciprocal relationship between humans and surrounding animals. The people of Kampung Naga are indigenous people located in Tasikmalaya who still adhere to the local wisdom they have today. Due to the absence of a study on ethnozoological studies in the Kampung Naga community, research was carried out on animal maintenance and control of rice pests which were included in the study of ethnozoological studies. The data collection techniques in this study were interview techniques and documentation with qualitative research methods. The results of the study found that the people of Kampung Naga have local wisdom regarding the control of agricultural pests, the main pests are brown planthopper, walang sangit, rats and birds as well as animal maintenance including chickens, goats, fish, guinea pigs and rabbits. This study aims to describe the study of ethnozoological studies of the people of Kampung Naga, Neglasari Village, Salawu District, Tasikmalaya Regency as a source of learning biology in the form of a booklet.ETNOZOOLOGI: STUDI KEARIFAN LOKAL MASYARAKAT ADAT KAMPUNG NAGA TASIKMALAYA